Respuesta :

Consider this:
sec t=1/ cos t
cos² t=(1-sin²t)
1/sin t=csc t

therefore:
sec²t / (sec² t-1)=(1/cos² t) / [(1/cos²t)  -1]=(1/cos² t) / [(1-cos²t)/cos²t]=
=[1/(1-sin²t)] / [(1-(1-sin²t)) / (1-sin²t)]=[1 / (1-sin²t)] / [(sin²t) / (1-sin²t)]=
=1/sin²t=csc ² t

Answer: sec²t / (sec²t-1)=csc²t
[tex] sec^2t / (sec^2 t-1)=(1/cos^2t) / [(1/cos^2t) -1]=(1/cos^2 t) / [(1-cos^2t)/c[/tex]

=[tex][1/(1-sin^2t)] / [(1-(1-sin^2t)) / (1-sin^2t)]=[1 / (1-sin^2t)] / [(sin^2t) / (1-sin^2t)][/tex]

[tex]=1/sin^2t=csc ^2 t[/tex]

[tex]Answer: sec^2t / (sec^2t-1)=csc^2t[/tex]